07.15 New mutated peptidylarginine deiminase from porphyromonas gingivalis a target in early ra citrullinates major ra-autoantigens. (1st March 2017) - Jenning, Madeleine; Marklein, Bianka; Ytterberg, Jimmy; Burmester, Gerd R; Skriner, Karl
Abstract : Background: Previous reports showed that peptidylarginine deiminase (PPAD) form Porphyromonas gingivalis (P.g.) is not able to citrullinate proteins internally. New mutated PPAD (mPPAD) from P.g. involved in periodontal disease (PD) cloned out of P.g. strain was characterised and analysed for its reactivity in sera from patients with systemic autoimmune diseases. Methods: Recombinant mutated PPAD from P.g. mPPAD mutations and citrullination sites were analysed by DNA sequencing and/or protein mass spectrometry. Autocitrullination activity it´s enzymatic-activity and human autoantigen protein citrullination was investigated by 2D-Elektrophoresis, MS, immunoblot analysis and ELISA. Furthermore we tested anti-mPPAD/cit-mPPAD with human sera (n=93) from early RA before and after onset of RA (n=30), established RA (n=32), SLE (n=16) and healthy blood donors (n=15) in ELISA assays. In RA mouse model collagen antibody-induced arthritis (CAIA), mPPAD-containing vesicles from P.g. were injected by intraperitoneal injection (IP). Results: Recombinant mPPAD lacks 43 amino acids at the N-terminus and exhibits so far two new amino acid mutations (aminoacid position 73 (F>L) and 447 (E>V). We were able to demonstrate, mPPAD is enzymatically active over a huge pH-range (3-10) and autocitrullinates at amino acid position 63 the arginine to citrulline. Moreover mPPAd citrullinates major autoantigens in RA (Fibrinogen, Vimentin and hnRNP-A2/B1) which are detectable by RA patient sera and specific anti-citrulline monoclonal antibodies. mPPAD citrullinates HeLa-protein extracts and these specific citrullinated proteins are recognised by RA patient sera. Anti-citrullinated mPPAD antibodies were detected in 41% (n=32) of patients with RA but not in SLE (n=16) and control sera (n=15). In a RA follow-up study (n=30), we detected nearly similar antibody-sensitivities for citrullinated mPPAD before and after onset of RA (13/20%). Only a minority (7%) of RA patients show higher mPPAD antibody levels after RA diagnosis. In the CAIA RA mouse model mPPAD containing P.g. vesicles when injected IP showed a TLR2-dependent protective anti-inflammatory effect like P.g. LPS and Lipomannan. Conclusions: Pg. infection and RA disease diagnosis occurs at different time points and Pg. infection induces a TLR2-dependent protective anti-inflammatory effect.We show the first time that mPPAD can citrullinate major human autoantigens internally and their immunologically and diagnostic relevance in RA.